Pregnancy in Prison: The consequences of the absence of prenatal care on the health of women in situations of deprivation of liberty (Research, Society and Development, 2021)
Introduction: initially, the situation of imprisonment related to pregnant women in prison is highlighted, such as unhealthy hygiene conditions, access to inadequate prenatal care during pregnancy, difficulty of access to wards, outpatient clinics and adequate medical care. We also highlight the issue of support for women during pregnancy, according to the Brazilian Federal Constitution, specifically in the National Policy of Attention to Women in Situations of Freedom (PNAMPE). This work aims to analyze the points about prenatal care for women in pregnancy when they are in a regime of deprivation of liberty. Justification: This research was conducted due to the worrisome prison situation in Brazil, especially in the state of Pará, where the number of women in prisons is greater than the supported capacity. The overcrowding in the prison environment hinders effective actions for a more individual attention to female prisoners and the realization of the aforementioned rights provided for in the Federal Constitution. Methodology: This is an integrative review of literature in full texts from the last 10 years. Results: It is possible to note the alarming situation that pregnant women face in prison units that do not offer prenatal care adequately. When researching on this theme it was evidenced the absence of articles, in the main databases, related to health issues of pregnant women in prison. Conclusion: we conclude that the unhealthy conditions of the penitentiaries bring serious risks to the serious risks to the health of children who are generated and born in this situation of deprivation of liberty and that pregnant women do not receive the basic attention of right during pregnancy and puerperium cycle, with the need for intersectoral and interprofessional work to ensure access to public policy with quality.